Essay Writing Challenges among First-Year Early Grade Education Students: A Case Study at Akenten Appiah-Menka University of Skills Training and Entrepreneurial Development - Afrifa-Yamoah, Daniel (International Journal of Language and Literary Studies, 2025)
Essay writing is a key component of language learning and development. Over time, writing has enhanced students’ linguistic proficiency and communication skills. However, students often encounter difficulties that hinder their ability to produce effective essays. This study aims to identify and assess the essay-writing challenges faced by first-year Bachelor of Early Grade Education students at the Akenten Appiah-Menka University of Skills Training and Entrepreneurial Development. A closed-ended questionnaire comprising 37 items was administered to 21 participants. The study examined five major challenges: plagiarism, grammatical errors, lexical difficulties, inadequate planning, and a lack of confidence. Findings revealed that lexical challenges were the most prevalent (M = 2.92), whereas grammatical errors were the least common (M = 2.3 on a 4-point Likert scale). The study concludes that the major obstacle to students’ writing performance is their limited vocabulary and difficulty using contextually appropriate diction. Recommendations are provided to improve students’ writing competence through targeted pedagogical interventions.